Women in Urban Local Government in Bangladesh: A Study on Narayanganj City Corporation - Jannatul Ferdous; Md. Nahidul Islam (Journal of Contemporary Governance and Public Policy, 2021)
Women's equal participation in politics is critical to women's advancement. This determination, however, is not to be made uniformly across the globe. Yet, in contemporary periods, it has witnessed a significant shift in women's political participation globally. The purpose of this paper is to gain a better understanding of women's overall participation, their socioeconomic status, and their valuable role in urban policy formulation and implementation in Bangladesh. In this analysis, primary and secondary data are integrated. Primary sources are referenced to substantiate theories and arguments asserted in the secondary literature, which are based on the case study of Narayanganj City Corporation. It is completed with the assistance of theories and contentions gleaned from secondary sources. Additionally, this study concludes with an examination of Bangladeshi women's position in the decision-making process. Another pressing need is to broaden the participation of women in political culture at the grassroots level. In urban areas, the City Corporation must interact with various government, autonomous, and semi-autonomous bodies. The situation of female ward councillors has deteriorated to the point where there is some ambiguity. Women's involvement in politics has been limited by a decline in financial capital and family support. Women can appeal to low-level politics thanks to a patriarchal viewpoint. In Bangladesh, women continue to struggle for equal rights and face political challenges. Societal norms enforce gender stereotypes. Religious restrictions are the most severe concern among Bangladesh's status issues, which have a complicated structure. Women are not politically socialized enough to participate in the political life of their country. The City Corporation's institutional rules and responsibilities are of little concern to women, and the existing regulations are insufficient. Therefore, the paper can reveal the actual scenario of women's representation and obstacles in the urban level of Bangladesh.